Loving vs. Virginia : a documentary novel - Powell, Patricia Hruby, 1951-; Strickland, Shadra (San Francisco, CA : Chronicle Books, 2016)
Written in blank verse, the story of Mildred Loving, an African American girl, and Richard Loving, a Caucasian boy, who challenge the Viriginia law forbidding interracial marriages in the 1950s.
Keywords: Loving, Richard Perry -- Trials, litigation, etc -- Juvenile fiction; Loving, Mildred Jeter -- Trials, litigation, etc -- Juvenile fiction; Loving, Richard Perry -- Trials, litigation, etc -- Fiction; Loving, Mildred Jeter -- Trials, litigation, etc -- Fiction; Interracial marriage -- Law and legislation -- Virginia -- Juvenile fiction; Interracial marriage -- Fiction; African Americans -- Fiction; Virginia -- Race relations -- Juvenile fiction; Virginia -- History -- 20th century -- Juvenile fiction; Race relations -- Fiction; Virginia -- History -- 20th century -- Fiction; Historical fiction